The noise awareness among hospital community due to traffic and construction noise in Hospital Raja Permaisuri Bainun - Md Nor, Ahmad Yunus Faeez (2018)
The Hospital Raja Permasuri Bainun Ipoh is the third largest hospital in Malaysia with a capacity of 990 beds, 16 operating room, 16 bed adult intensive care unit, 8 bed coronary care units, 17 bed intensive care unit of a child (PICU) and 20 extra neonatal care unit. Due from that, the identification about surrounding of hospital is needed. This research investigates the traffic noise and construction noise and the perception it has on the community of Hospital Raja Permaisuri Bainun, Ipoh. The selected study area was delimited by traffic noise on the Raja Ashman Shah Road and construction on the hospital block. A sound level meter was used to measure the both noise at 3 different measuring points within the study area. Measurements were taken during the day (7am to 7pm) and at night (8pm-11.30pm) in order to establish the noise around the hospital. The data have been analyzed using the Microsoft Excel 2007 to get the average of noise produced. A 29-item noise-perception –related questionnaire was used to establish the perception of noise pollution on the respondents. A 150 randomly chosen participants within the hospital community were answers the through quantitative method. On the completion of this research, it was established that the noise surround the hospital are exceed the permissible noise level limits based on Department of Environment Malaysia. Based on the result, the majority of the participants are having bad perceptions with support from literature review about the noise pollution causing around the hospital that it affected them during current and after receive the noise. The finding contributes to increase the awareness among the stakeholders.